Abstract and Poster: October 7-11, 2022, The 9th Congress of the EUROPEAN ACADEMY OF PAEDIATRIC SOCIETIES, Barcelona & Online; A Joint Scientific and Educational Event of EAP, ESPNIC and ESPR - Anwar, Kazi Selim (The Journal of Ad-din Women’s Medical College, 2023)
Background and Aim: Since community-based research on childhood tuberculosis (CTB) is scarcely conducted in Bangladesh, we conducted this KAP (knowledge, attitude and practice) door-to-door survey on CTB in 18 rural-villages of Khulna (relatively ignored and lessfocused). 9th Congress of the European Academy of Pediatric Societies 2281 Poster Viewing Abstracts Methods: Utilizing a hybrid-designed method we conducted this KAP-survey among 434 parents to assess their knowledge-score, attitudinal-trend and practice- level on the prevention/control of CTB, Quantitively, potentials of CTB control-dynamics were measured among domiciliaryhealth-care service (HCW) providers to strengthen DOTS qualitatively (KII-method: Priori-Code list/Matrix). Results: Most respondents were young-females (90%) from lower/mid socio-economic status being more literate (34%) than men (26%). Poverty, distantly-located health-care-centers, poor-household-income remained causes of non-compliance in health-care-seeking- behavior. Mean knowledge-score was 2.94±0.8: 59% had low, 35% good and 10.5% adequate. Respondent’s attitude: Likert-scale on CTB-prevention/control was positive in 77%. To answer if CTB is curable:47% said sometime,30% always; 23% thinks CTB be prevented by ‘avoiding CTB-patient-contact, 23% avoiding open-coughing or spitting-o/dispose sputum safely, while 45% had no idea. Our observation yielded kitchen (dry-smoky fuel) in>80% households attached to child’s living/bed that may cause/aggravate CTB. Of all KII involving community-based HCWs, Pediatricians/Administrators, revealed CTB could be latent/underdiagnosed so actual CTB-prevalence may be more than actual-reporting. It became di!cult to detect C/TB due to parental misunderstand on proper diagnosis and care. Conclusions: Our *ndings will further assist the policy makers towards a better/ robust strategic planning of CTB-prevention &/or control. Our data will add prudent values in further strengthening of preventive strategies treatment planning and control measures against CTB The Journal of Ad-din Women's Medical College; Vol. 10 (2), July 2022; p 67-68